A Checklist to Avoid Pilot Failures : Lessons from a Set of Women’s Economic Empowerment Initiatives - Johansson de Silva, Sara; Paci, Pierella; Posadas, Josefina (Taylor and Francis, 2014)
Pilot programs have gained significance in donor-supported development interventions because of the growing emphasis on measuring impact. The Results-based initiatives (RBI) were conceived as pioneering pilots expected to acquire rigorous evidence on effective interventions to foster women’s economic empowerment. However, they fell short of providing clear or generalizable conclusions on women’s economic empowerment due to design and implementation problems. The RBI nevertheless offer important lessons on common traps in pilot design and implementation. This article synthesizes 10 lessons from the RBI as a checklist to avoid pilot failure, intended for practitioners in any area of development.